"Because you've lived in different places all your life" – How mobility trajectories create cross-border entrepreneurial opportunities for migrants in Switzerland. Issue 129 (February 2022) - Mittmasser, Christina
Highlights: Migrant entrepreneurs in Switzerland often use resources in multiple countries. This is related to their complex biographies transcending the classic home-host-country-trajectory. This paper uses a time-geographic and biographic approach. It depicts the complex evolution of cross-border resources throughout the history of migration. It also captures the constraints experienced by different groups of migrants over time. Abstract: The activities of migrant entrepreneurs increasingly extend beyond national borders as they travel and move goods between countries. Yet, research still portrays a static and homogeneous picture of the phenomenon which disregards complex biographies, evolving along multiple places over time, and cross-border activities beyond the origin and destination country. In response, this article uses a time-geographic and biographic approach which allows for a more dynamic investigation of the different localities involved in migrants' entrepreneurial projects and the evolution of cross-border resources throughout their history of migration. The presented study is based on ethnographic observations and biographic interviews, including trajectories traced on geographic maps, of 34 migrants with diverse backgrounds in Zurich, Switzerland. Because most research participants have multiple migration experiences and are female, it provides insights into understudied groups within the field. The article introduces a typology of three different kinds of cross-border migrant entrepreneurship. In contrast to the classic literature, it highlights that the cross-border engagement of migrants often transcends the origin–destination binary. Knowledge of economic and institutional environments, professional and intimate contacts, as well as other competences that interviewees have developed within different localities and episodes of their mobile biographies, become important resources in this regard. Moreover, the study offers a nuanced view on the constraints experienced and strategies employed by different groups of migrants according to their position in society.